2013
DOI: 10.1166/jnn.2013.6882
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-Gallate (EGCG) Inhibits Cell Proliferation and Migratory Behaviour of Triple Negative Breast Cancer Cells

Abstract: Previous studies indicate that green tea extract may inhibit breast cancer progression by blocking angiogenesis, although the molecular mechanisms are not well defined. Epigallocatechin-3-gallate (EGCG) is the major biologically active component of green tea. In this study we evaluated the cell proliferation and relative gene expression of vascular endothelial growth factor (VEGF) expression on Hs578T human breast cancer cell line at 24, 48 and 72 hours after 10 microM of EGCG treatment. Also, we evaluated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(46 citation statements)
references
References 0 publications
1
44
0
1
Order By: Relevance
“…Indeed, EGCG has been shown to possess anti-oxidative (8), antimicrobia (9), and anticarcinogenic (10) effects, in addition to reducing the risk for cardiovascular diseases (11), diabetes (12), neurodegenerative diseases (13) and cancer. The anticancer effects of EGCG on different cancer events have been assessed: EGCG reversed the progression of colon carcinomas by decreasing methylation (14), reduced mRNA expression and showed anti-proliferative potential in cervical cancer cells (15), induced apoptosis in skin cancer cells (16), and inhibited motility and angiogenesis of lung and breast cancer cells (1719). In addition, the effect of EGCG on suppressing division and inducing apoptosis of cancer cells is mediated by several signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, EGCG has been shown to possess anti-oxidative (8), antimicrobia (9), and anticarcinogenic (10) effects, in addition to reducing the risk for cardiovascular diseases (11), diabetes (12), neurodegenerative diseases (13) and cancer. The anticancer effects of EGCG on different cancer events have been assessed: EGCG reversed the progression of colon carcinomas by decreasing methylation (14), reduced mRNA expression and showed anti-proliferative potential in cervical cancer cells (15), induced apoptosis in skin cancer cells (16), and inhibited motility and angiogenesis of lung and breast cancer cells (1719). In addition, the effect of EGCG on suppressing division and inducing apoptosis of cancer cells is mediated by several signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…EGCG is a natural compound with a wide array of biological activities. In fact, EGCG has been shown to have antitumor, antiangiogenic and antiinflammatory effects [15][16][17][18][19][20][21][22][23][24][25]. This makes EGCG a potentially interesting candidate for screening studies searching for synergistic combinations.…”
Section: Discussionmentioning
confidence: 99%
“…Epigallocatechin-3-gallate (EGCG) is an abundant polyphenol in green tea leaves with a number of biological activities, including antiangiogenesis [5], anticarcinogenesis [16][17][18], antimetastasis [19], as well as cancer chemoprevention, among others [20]. Furthermore, our group has previously shown that EGCG is a potent antiinflammatory compound [21,22] targeting histidine decarboxylase [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, our team has shed a new light on the field 11,12 by different conjugation procedures for these therapeutics. Overcoming this threshold bears major clinical significance in oncology and hematology, as developing nonviral gene delivery vehicles will bring new patient-tailored drugs within reach ( Figure 1).…”
Section: Drug Nanocarriers In Cancer Pharmacologymentioning
confidence: 99%